Realm of paradise - Boey, Kim Cheng (2020)
The carcass sits astride the motorbike, fastened to the saddle by ropes, its pale pink bulk having ridden pillion in the fine drizzle to its final place of immolation. A faint hint of a smile hovers over its peaceful face, its shut, long-lashed eyes, its creased forehead and endearing snout, and even its flappy ears giving it somewhat a content, eerily human look. Perhaps not incongruously, Ted Hughes’s “View of a Pig” comes to mind. As I try to recall the magnificent ending, the helmeted driver loosens the lashings around the pig, and under the supervision of the women he and three other men grab the trotters and heave the weight on their shoulders, and march it funereally up the wet marble steps to the trestle table draped with a Coca Cola plastic sheet, and ceremoniously lay the cargo down. The Vietnamese matrons take care of the details, and direct their men in adjusting the pig till it looks presentable, dignified, a fitting sacrificial feast for the hungry spirits of the dead soldiers.